A Naming Game-Based Method for the Location of Information Source in Social Networks. (27th April 2020) - Yang, Xue; Zhu, Zhiliang; Yu, Hai; Zhao, Yuli
Abstract : We study herein the problem of the location of the information propagation source in social networks based on the network topology and a set of observations. We propose a concise and novel method to accurately locate the source of information using naming game theory. This study introduces the design of a dynamic deployment method that reduces considerably the number of observations and the time needed to locate the source. Moreover, it calculates the probability of each node that acts as a source based on the information provided by observations. This method can be potentially applied to various information propagation models. The simulation results reveal that the method is able to estimate the information source within a small number of hops from the true source.